All in the mind. (Economist, 2023)
The article features Great Britain's National Cyber Force (NCF) and its commander James Babbage. Also cited are the NCF's duties and responsibilities like hacking computers and their networks and influencing the behaviour of people or groups, and the purpose and principles of offensive cyber operations as cited in the NCF's document "Responsible Cyber Power in Practice."